Cross-Cultural Filmmaking as a Process of Self-Reflection: Filming Native Americans within Central European Space’s Prevailing Imagery of the “Noble Savage” - Šavelková, Lívia (My University, 2017)
In Said´s notion of “Orientalism” as a set of discursive practices through which the West structured the imagined East, the Czech Republic (or former Czechoslovakia) in particular, and so called Eastern Europe in general, has been viewed by “the West” as a space inhabited by “exotic other”. The former socialist countries (and the so called post-socialist countries) have been constructing their own “Orients” and “exotic others” as well including Noble Savage stereotype of Native Americans. This paper focuses on a visual (re)presentation of a meeting between people who might have mutually constructed each other as the “exotic other”. Based on filming of a visit of a Native American sport team competing in the Czech Republic, the paper would like to discuss who are the “exotic ones” and for whom and the methodological issues related to the creation of the cross-cultural ethnographic films.
Filmování jako proces sebereflexe ve středoevropském „prostoru ušlechtilého divocha“
Keywords: cross-cultural filmmaking; Native Americans; Noble Savage; Central Europe; colonialism; film; mezikulturní filmování; stereotyp ušlechtilého divocha; indiáni; kolonialismus; Střední Evropa